The Influence of Leverage and Capital Intensity on Effective Tax Rate (ETR) Through Profitability - Laksmitasari Azizah, Nurifa; Farras Mufidah, Imtiyaz (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The company aims to maximize profits by implementing various methods, one of which is tax management through the effective tax rate (ETR) in order to minimize the effective tax rate of a company. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2018 period with a total of 185 companies. Sampling was carried out using the purposive sampling method and obtained a final sample of 93 companies. The data analysis technique used in this study is descriptive statistical analysis and inferential statistical analysis, namely regression analysis with moderating variables using the absolute difference value test method. Based on the results of the study, it shows that leverage affects the effective tax rate, so the higher the leverage, the higher the effective tax rate. Capital intensity affects the effective tax rate, so the higher the capital intensity, the higher the effective tax rate. Profitability has an effect on the effective tax rate, so it can be said that the higher the profitability, the higher the effective tax rate. Profitability is able to moderate the effect of leverage and capital intensity on the effective tax rate.